2001
DOI: 10.1002/mc.10014
|View full text |Cite
|
Sign up to set email alerts
|

Different mutation status of the β‐catenin gene in carcinogen‐induced colon, brain, and oral tumors in rats

Abstract: Mutations in the region corresponding to the N-terminal phosphorylation sites (codons 1-51) of the rat beta-catenin gene (Ctnnb1) were investigated in rat colon tumors induced by 1-hydroxyanthraquinone (1-HA) plus methylazoxymethanol (MAM) acetate, by using polymerase chain reaction (PCR)-single-strand conformation polymorphism (SSCP) analysis. The beta-catenin gene was also screened for mutations in rat brain and oral tumors induced by ethyl nitrosourea (ENU) and 4-nitroquinoline 1-oxide (4-NQO), respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…Our data support the hypothesis that MAM-induced O 6 -mG DNA lesions alter purine metabolism and modulate cell-signaling pathways associated with both neurodegeneration and cancer. While MAM does not induce brain tumors in singly treated adult mice, the genotoxin consistently triggers tumors in peripheral organs, notably the intestine [37], [38]. The prominent modulation of “cancer genes” in the “tumor-insensitive” brains of MAM-treated adult animals suggests that perturbations of these genes in the brain have consequences other than cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Our data support the hypothesis that MAM-induced O 6 -mG DNA lesions alter purine metabolism and modulate cell-signaling pathways associated with both neurodegeneration and cancer. While MAM does not induce brain tumors in singly treated adult mice, the genotoxin consistently triggers tumors in peripheral organs, notably the intestine [37], [38]. The prominent modulation of “cancer genes” in the “tumor-insensitive” brains of MAM-treated adult animals suggests that perturbations of these genes in the brain have consequences other than cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although molecular alterations are infrequent in 4-NQOinduced rat tongue carcinomas [59,60], our recent study has revealed that 4-NQO treatment for eight weeks could more rapidly induce (within eight weeks) tongue dysplasia, squamous cell papillomas and squamous cell carcinoama in male and female transgenic rats carrying the human c-Ha-ras proto-oncogene [61], when compared to wild rats, suggesting that alterations of c-Ha-ras are involved in 4-NQO- induced tongue carcinogenesis, especially the early phase of carcinogenesis. Interestingly, this transgenic rat also develops taste bud tumors [62,63].…”
Section: Animal Models Of Oral Carcinogenesismentioning
confidence: 97%
“…29,30) Mutations were found in codons 33, 37, 41, and 45, encoding serine and threonine that are direct targets for phosphorylation by GSK-3β. Also reported were alterations of codons 32, 34, and 35, neighboring serine and threonine residues, possibly resulting in conformational changes and abnormal phosphorylation of the β-catenin protein.…”
Section: Sermentioning
confidence: 99%